Uncovering the anti-proliferation mechanism and bioactive compounds in red kidney bean coat against B16-F10 melanoma cells by metabolomics and network pharmacology analysis. Issue 2 (30th January 2019) - Nie, Jia-Hui; Huang, Jian-Xiang; Wu, Qing-Rong; Qin, Xue-Mei; Li, Zhen-Yu
Abstract : In this study, coat (RKBC) and kernel (RKBK) extracts of red kidney bean were prepared, and their chemical compositions and potential anti-cancer activity against B16-F10 cells were evaluated. Abstract : In this study, coat (RKBC) and kernel (RKBK) extracts of red kidney bean were prepared, and their chemical compositions and potential anti-cancer activity against B16-F10 cells were evaluated. Then the anti-proliferation mechanisms of the active RKBC extract were investigated by flow cytometry analysis, cellular metabolomics, network pharmacology and western blotting. The RKBC extract inhibited B16-F10 cell proliferation and migration in a dose-dependent manner. Further analysis showed that RKBC induced G1 and G2/M phase arrest, and triggered apoptosis and vacuolization. Mechanistically, RKBC significantly increased the cellular content of cGMP, decreased the levels of AKT1/2/3 and cleaved-MMP2, and up-regulated the expression of Bcl-xl. Besides, network pharmacology revealed that RKBC potentially influenced the cell cycle via the regulation of CDK2 and CDK4. Finally, quercetin might serve as the major active component in the RKBC extract. In conclusion, our study showed the potential of the RKBC extract for the prevention or treatment of melanoma.